Space dependency of chemical attributes in an area with sugarcane plantation in Pereira Barreto, SP - Costa Campos, Milton Cesar; Marques Junior, Jose [UNESP]; Tadeu Pereira, Gener [UNESP]; de Souza Freitas, Eriberto Vagner (Univ Federal Ceara, 2007)
The behavior of the chemical attributes is directly influenced by superficial flow and water movement inside the soil. This work aimed to study the space dependency of chemical attributes in an area with sugarcane plantation in Pereira Barreto, SP. An area of 530.67 hectares was mapped using an equipment of Global Positioning System and obtaining a Digital Elevation Model. A set of 134 soil samples were collected every seven hectares in the depths of 0-0.25 m and 0.80-1.00 m. The pH, organic matter (OM), Ca, Mg, K, BS, CEC and base saturation (BS) were analyzed. All the chemical attributes presented similar behavior in the superficial and subsuperficial layer of the soil, which provided better visualization and definition of the homogeneous tillage zones.
Keywords: Geostatistics; spatial variability; Sugarcane